EFFECTS OF OLIVE LEAF EXTRACT (OL EA EUROPEA L.) ON GROWTH PERFORMANCE, BLOOD METABOLITES AND ANTIOXIDANT ACTIVITIES IN BROILER CHICKENS UNDER HEAT STRESS - M. J. Agah; M. T. Mirakzehi; H. Saleh (Journal of Animal and Plant Sciences, 2019)
The aim of the study was to investigate the effects of olive leaf extract (Olea europea L.) (OLE) and α-tocopheryl acetate (α-Toc) on growth performance, nutrient digestibility, blood metabolites and antioxidant activities in heat exposed broiler chickens. Total 200 day-old male Ross 308 chicks were distributed in a completely randomized experimental design, with four treatments and five replicates of 10 birds each. Heat stress was applied for 5 h (33°C) from 28 to 42 days. The treatments were: negative control (without α-Toc and OLE; NC); a positive control (with 250 mg kg-1 of α-Toc; PC) and diets with 200 or 400 mg of OLE/kg of diet (OLE1and OLE2, respectively). Heat stress (32± 2°C) was applied daily for all the birds. On day 42, blood samples were taken from two birds per replicate. Chromic oxide was used as inert ileal digestibility markers. The evaluated treatments did not significantly affect body weight gain, feed intake and feed conversion ratio. Ileal digestibility of energy, crude ash, Crude Protein, and phosphorus showed a linear increase with supplementation of OLE and α-toc (p≤0.05). Cholesterol, triglyceride, Alanine transaminase (ALT) and aspartate aminotransferase (AST) in blood were significantly decreased when chickens were fed diets containing OLE (P ≤ 0.05). Plasma lipid peroxidation leve land glutathione peroxidase activities were reduced in chickens fed diets supplemented with OLE and α-Toc (P ≤ 0.05). In conclusion, Supplementation of olive leaf extract to broiler diets as antioxidant components could improve the antioxidant status and reduction in the stressor index of heat stressed broilers.
Keywords: Phenoliccontent; oliveleaf; ±-tocopherylacetate; broiler; heatstress